2021
DOI: 10.1371/journal.pone.0257421
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of COVID-19 recovered patients in Bangladesh

Abstract: Coronavirus Disease-2019 (COVID-19) quickly surged the whole world and affected people’s physical, mental, and social health thereby upsetting their quality of life. Therefore, we aimed to investigate the quality of life (QoL) of COVID-19 positive patients after recovery in Bangladesh. This was a study of adult (aged ≥18 years) COVID-19 individuals from eight divisions of Bangladesh diagnosed and confirmed by Reverse Transcription-Polymerase Chain Reaction (RT-PCR) from June 2020 to November 2020. Given a resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 32 publications
7
34
0
1
Order By: Relevance
“…The study excluded those treated for COVID-19, pregnant women, and the critically ill. In our earlier nationwide study, we collected a list of COVID-19 positive cases from the whole country [ 25 ]. We randomly approached 4584 patients and then completed an interview of 3,244 participants from the list.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study excluded those treated for COVID-19, pregnant women, and the critically ill. In our earlier nationwide study, we collected a list of COVID-19 positive cases from the whole country [ 25 ]. We randomly approached 4584 patients and then completed an interview of 3,244 participants from the list.…”
Section: Methodsmentioning
confidence: 99%
“…We randomly approached 4584 patients and then completed an interview of 3,244 participants from the list. The detailed study methods were described elsewhere [ 25 ]. Among those 3,244 participants, we found 322 HCWs and considered them recruited in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The current study’s sample size was 444 (222 in each group). In our earlier nationwide study [ 22 ], we collected the list of COVID-19 positive cases from the Institute of Epidemiology and Disease Control and Research (IEDCR) which contained a list of COVID-19 positive cases from the whole country. We approached randomly to 4584 patients from the list, among them 3244 patients responded with a response rate of about 71%.…”
Section: Methodsmentioning
confidence: 99%
“… 28 , 29 Surveys on such conditions in Vietnamese COVID-19 patients are lacking and no studies on this topic have been found. Understanding the psychological responses of this most vulnerable population, as well as related factors, will allow authorities to provide suitable measures to support psychological treatment and restore the community's quality of life, 30 , 31 ensuring and maintaining national labour resources in the new post-crisis period. Therefore this study was conducted to measure the prevalence rates of mental problems, including PTSD, anxiety, depression and related factors, among COVID-19 patients in Vietnam.…”
Section: Introductionmentioning
confidence: 99%